Methylation of Imprinted Genes in Sperm DNA Correlated to Urinary Polycyclic Aromatic Hydrocarbons (PAHs) Exposure Levels in Reproductive-Aged Men and the Birth Outcomes of the Offspring - Yang, Jia; Lu, Zhaoxu; Liu, Zhichao; Wang, Li; Qiang, Mei (Frontiers in Genetics, 2021)
Polycyclic aromatic hydrocarbons (PAHs) are known environmental pollutants. Studies are very limited regarding the impacts of paternal PAHs exposure on birth outcomes as well as the underpinning mechanisms in human. In this study, 302 reproductive-aged males (22 - 46 years old) were enrolled and demographic informatics data were obtained by questionnaires. The levels of urinary hydroxyl metabolites of PAHs (OH-PAHs) were assessed by ultra-high performance liquid chromatography-tandem mass spectrometry; and methylation levels of the imprinting genes H19, Peg3 and Meg3 of sperm DNA were evaluated via bisulfite pyrosequencing. The analysis of the correlation between urinary OH-PAHs levels and methylation levels of imprinting genes in sperm DNA showed that OH-PAHs are correlated with some CpG sites in H19, Peg3 and Meg3. To further investigate an association of urinary OH-PAHs with birth outcomes, follow-up study of wives of these subjects has been carried out for 1-3 years. As the result, a total of 157 babies were recorded. The birth outcomes parameters included birth weight (BW), length (BL) and ponderal index (PI). The further analysis of generalized estimating equation indicated a negative correlation between urinary total OH-PAHs levels and newborn BW (β = -0.081, p = 0.020); but this association did not been found for BL and PI. Furthermore, a logistic regression analysis was employed for examining associations of the methylation of imprinting genes with birth outcomes parameters, which indicated a negative correlation between BW and H19, namely, each unit percent (%) elevation in methylation of H19 (but not Peg3 and Meg3) was significantly associated with 0.135g reduction of BW (β = -0.135; 95% CI 0.781 - 0.978). Putting together, these results show that paternal non-occupational environmental exposure to PAHs impacted on newborn BW. And imprinting gene H19 methylation may be involved in the underlying mechanisms. This study in human population adds a support for previous animal study and implies that environmental impact on the offspring through paternal pathway.